Pengaruh Kualitas Layanan Sertifikat Elektronik Terhadap Kepuasan Masyarakat Pada Kantor Pertanahan Kabupaten Gowa - Yuliani, Yuyun; Suhendra, Suhendra; Sari, A Ratna (Patria Artha Management Journal, 2025)
This study aims to determine the influence of electronic land certificate service quality on public satisfaction at the Land Office of Gowa Regency. The background of this research is driven by a national phenomenon regarding the low quality of public services in several regions of Indonesia, although Gowa Regency is not included in those areas. The digitization of land services through the implementation of electronic certificates is a modernization effort whose effectiveness must be evaluated, especially from the users' perspective.This research uses a quantitative approach with simple linear regression analysis. The sample consisted of 100 respondents who were users of electronic certificate services in Gowa Regency. Service quality was measured using the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy.The results show that service quality has a positive and significant effect on public satisfaction, with a significance value of 0.000 and a regression coefficient of 0.824. This indicates that the higher the public’s perception of service quality, the higher the level of satisfaction experienced. However, there is still public skepticism regarding the legal strength of electronic certificates, which poses a unique challenge to the implementation of digital services.Therefore, efforts to improve service quality must be accompanied by adequate public education on the legality and security of electronic services, so that public trust in digital land services can continue to grow.